Report of a New Larval Host Plant of Galleria mellonella (Linnaeus, 1758) from Kolkata, West Bengal, India (Lepidoptera: Pyralidae, Galleriinae) - Das, Srinjoy; Chakraborty, Kaustav (SHILAP Revista de lepidopterología, 2024)
In this study, we report for the first time a new larval host plant Cassia fistula L. for Galleria mellonella (Linnaeus, 1758) from Kolkata, West Bengal, India. Galleria mellonella is an established pest of beehives and till date, its larvae were known to feed only on the wax comb of Apis sp.,and destroy it. For this reason, beekeeping enterprises face high economic losses. Our finding opens a scope for extensive surveys in areas surrounding apiaries in order to quantify infestations in C. fistula which might provide a new insight in the pest management practices for G. mellonella.